Construct validity of Subjective Well-being by Confirmatory Factor Analysis (CFA) in Indonesian caregivers of Intellectually disabled children - Ratnasari, Risa Dwi; Truong, Vuong; Sumiati, Neneng Tati (JP3I (Jurnal Pengukuran Psikologi dan Pendidikan Indonesia), 2020)
Bringing up a child with disabilities has particular challenges and demands as these children's disabilities may cause certain impacts on their caregivers' well-being. In most of the studies, caregivers exhibited high scores of negative emotions that led to low subjective well-being. The effort to improve caregivers' well-being has been being carried out and one of the ways through subjective well-being research. Diener et al. (2009) define Subjective Well-Being (SWB) as the person’s evaluation of their life events in terms of cognitive and affective aspects. The higher rating score of these aspects, the higher level of SWB of the person. The aspects of SWB could be well measured if the instrument has good psychometric properties. The validity of the instruments is crucial to produce good quality research. In the present study, we examined the construct validity of the SWB using Satisfaction with Life Scale (SWLS) and Scale of Positive and Negative Experience (SPANE) scales. The data was collected from 209 parents who had children with intellectual disability in Tangerang and Jakarta. The construct was validated by exploratory factor analysis (EFA) and Confirmatory Factor Analysis (CFA) in the software R version 3.6.2. The EFA results showed that the construct consisted of four factors: one for the cognitive aspect, one for positive affect, and two for negative affects. The CFA results further demonstrated that this model fitted the empirical data.